Quantum Cryptography for Enhanced Security in Cloud-Based Systems - Kari Elisabeth Larsen; Lars Magnus Johansen; Olav Alexander Pedersen (International Journal of Electrical Engineering, Mathematics and Computer Science, 2024)
Cloud-based systems are increasingly vulnerable to a range of cybersecurity threats, driving the need for advanced encryption methods. This paper investigates the potential of quantum cryptography in securing cloud environments, focusing on the use of quantum key distribution (QKD) protocols. By leveraging the principles of quantum mechanics, the study demonstrates significant improvements in data security, offering enhanced protection against eavesdropping and paving the way for more resilient cloud security frameworks.